Facile Fabrication of Magnesium Oxide with Different Morphology - Wang, Guosheng; Zhang, Feiyan; Jun Wang, Kang; Kong, Changyi (Asian Journal of Chemistry, 2013)
Magnesium oxide nanomaterials have been fabricated using industrial magnesium oxide as raw material via precipitation. The XRD result indicated that basic magnesium carbonate [4MgCO3·xMg(OH)2·yH2O, x = 0-1, y = 3-8] was obtained when aqueous magnesium carbonate was heated from 55-95 ºC. According to SEM measurement, different morphologies of basic magnesium carbonate [4MgCO3·xMg(OH)2·yH2O], including rod, cotton stick and petal, could be achieved via varying the reaction temperature. And the morphologies were not destroyed after calcination of 4MgCO3·xMg(OH)2·yH2O to magnesium oxide. Iodine adsorption method was used to test the activity of prepared magnesium oxide. The result showed that high active magnesium oxide was obtained at 85 ºC of reaction temperature, the iodine adsorption value of magnesium oxide was as high as 198 mg/g of MgO.